2018
DOI: 10.1111/sjtg.12228
|View full text |Cite
|
Sign up to set email alerts
|

Mangrove forest dynamics in Tanintharyi, Myanmar from 1989–2014, and the role of future economic and political developments

Abstract: Mangrove forests in Southeast Asia provide many ecosystem services, though are experiencing extensive deforestation, especially in Myanmar. Recent political and economic reforms in Myanmar are projected to further increase development pressures on natural resources. Mangrove forests in the southern state of Tanintharyi have largely been spared clearance because of poor infrastructure and a volatile security situation, though this may change with plans for economic expansion. We quantified land cover dynamics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 46 publications
1
17
1
Order By: Relevance
“…There are also some inconsistencies at the state/region level. For instance, while our 2014 mangrove forest cover estimate for Tanintharyi (0.24 million ha) and the estimate of Gaw, Linkie, and Friess () for the same state and year were relatively close (0.25 million ha), this was not necessarily the case for the year 2000 (0.28 and 0.26 million ha, respectively). For the years 2015 and 2016, De Alban, Connette, Oswald, and Webb () and Connette, Oswald, Songer, and Leimgruber () estimated the state's mangrove area to be 0.34 and 0.24 million ha, respectively.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…There are also some inconsistencies at the state/region level. For instance, while our 2014 mangrove forest cover estimate for Tanintharyi (0.24 million ha) and the estimate of Gaw, Linkie, and Friess () for the same state and year were relatively close (0.25 million ha), this was not necessarily the case for the year 2000 (0.28 and 0.26 million ha, respectively). For the years 2015 and 2016, De Alban, Connette, Oswald, and Webb () and Connette, Oswald, Songer, and Leimgruber () estimated the state's mangrove area to be 0.34 and 0.24 million ha, respectively.…”
Section: Discussionmentioning
confidence: 53%
“…mar's mangrove forest cover.There are also some inconsistencies at the state/region level. For instance, while our 2014 mangrove forest cover estimate for Tanintharyi (0.24 million ha) and the estimate ofGaw, Linkie, and Friess (2018) for the same state and year were relatively close (0.25 million ha), this was not necessarily the case for the year 2000…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…Rubber plantations are expected to further expand given the Myanmar government's plans to increase rubber acreage and production capacity, as well as the availability of suitable vacant land area in the rubber-growing regions (Vagneron et al 2017). The systematic transitions of mangrove losses/gains to/from water bodies suggest a potentially burgeoning threat of aquaculture development in all sub-national units, previously only speculated on by previous studies in Myanmar (Oo 2002, Giri et al 2008, Maung 2012, Zöckler et al 2013, Richards and Friess 2015, Gaw et al 2018, Veettil et al 2018. Expansion of aquaculture began in the late 1990s (Maung 2012) and although the total area converted remains low, future expansion is expected owing to increased international opportunities afforded by access to international markets .…”
Section: Underlying Drivers Of Mangrove Cover Changementioning
confidence: 94%
“…A recent and revised Landsatderived estimate of mangrove cover and change for Myanmar highlighted a growing mangrove deforestation crisis, and demonstrated the need to develop ground-up datasets and avoid sub-setting global datasets for national-level mangrove estimates (Estoque et al 2018). Other studies have demonstrated the importance of reporting gross land cover statistics when evaluating change dynamics, including mangroves (Thomas et al 2017, Estoque et al 2018, Gaw et al 2018, De Alban et al 2019. This is because gross land cover change estimates provide essential information on transitions among land cover classes unavailable through net change studies, leading to a more robust analysis of the drivers of land cover change (Pontius et al 2004, Aldwaik and, which is especially important for relatively dynamic mangrove communities since they are amenable to rapid deforestation (loss) but can also rapidly regenerate (gain) when biophysical conditions are appropriate (Lewis 2005, Loon et al 2016.…”
Section: Introductionmentioning
confidence: 99%